Awangardowe i ariergardowe tradycje w nowej polskiej poezji na przykładzie twórczości Andrzeja Sosnowskiego - Tabaszewska, Justyna (Zagadnienia Rodzajów Literackich, 2019)
This article attempts to answer the question of whether we can describe contemporary poetry as avant-garde? The author recognizes problems associated with defining the avant-garde as a historical phenomenon and proposes — resorting to Marjorie Perloff ’s concepts — a new way of interpreting contemporary poetry as an arrière-garde reconstruction of avant-garde poetics. The oeuvre of Andrzej Sosnowski is analyzed as an interesting example of how the strategy of unoriginality can be incorporated into a new model of arrière-garde poetics.